FOREIGN INSTITUTIONAL SHAREHOLDERS AND CORPORATE PAYOUT POLICY - Setiawan, Rahmat; Christiana, Nova; Singh, Sanju Kumar (Jurnal Akuntansi dan Keuangan Indonesia, 2020)
This study examines the effect of foreign institutional shareholders (FIS) on corporate payout policy. The study employs 97 Indonesian manufacturing firms listed on the Indonesia Stock Exchange period 2011-2015. Multivariate Tobit and Logit are employed to estimate the model. The result confirms the bird in the hand theory that FISs need assurance of their investments in the emerging market. FIS has a monitoring role over the firms since they have the ability to detect the firm’s quality and the agency problem within. The result confirms that the presence of the FIS in the firm has a positive and significant effect on both measures of corporate payout policy, dividend to net income and dividend to total asset. The presence of the FIS increases the propensity of the firm to pay a dividend.